Combining biomechanical stimulation and chronobiology: a novel approach for augmented chondrogenesis? - Vágó, Judit; Takács, Roland; Kovács, Patrik; Hajdú, Tibor; van der Veen, Daan R.; Matta, Csaba (Frontiers in Bioengineering and Biotechnology, 2023)
The unique structure and composition of articular cartilage is critical for its physiological function. However, this architecture may get disrupted by degeneration or trauma. Due to the low intrinsic regeneration properties of the tissue, the healing response is generally poor. Low-grade inflammation in patients with osteoarthritis (OA) advances cartilage degradation, resulting in pain, immobility, and reduced quality of life. Generating neocartilage using advanced tissue engineering approaches may address these limitations. The biocompatible microenvironment that is suitable for cartilage regeneration may not only rely on cells and scaffolds, but also on the spatial and temporal features of biomechanics. Cell-autonomous biological clocks that generate circadian rhythms in chondrocytes are generally accepted to be indispensable for normal cartilage homeostasis. While the molecular details of the circadian clockwork are increasingly well understood at the cellular level, the mechanisms that enable clock entrainment by biomechanical signals, which are highly relevant in cartilage, are still largely unknown. This narrative review outlines the role of the biomechanical microenvironment to advance cartilage tissue engineering via entraining the molecular circadian clockwork, and highlights how application of this concept may enhance the development and successful translation of biomechanically relevant tissue engineering interventions.